Duke Teaching and Leading EBP: A Workshop for Educators and Champions of Evidence-Based Practice - Thrall, Grace; von Isenburg, Megan; Keitz, Sheri; Schardt, Connie; Cantrell, Sarah; Owens, Tom; Young, Larry; Fox, Jamie (2024)
Abbreviated workshop manual for the 2024 Duke Teaching & Learning Evidence-Based Practice Workshop. Note: this manual is an abbreviated version of the full 2024 workshop manual (http://hdl.handle.net/2193/SQ87BV16T)